PENGARUH PELAYANAN PRIMA TERHADAP KEPUASAN PENYANDANG DISABILITAS DALAM PENDATAAN ADMINISTRASI KEPENDUDUKAN - Rahmat, Nur Anita; Mahsyar, Abdul; Sudarmi, Sudarmi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of this research is to describe and explain the influence of excellent service on the satisfaction of people with disabilities in population administration data collection at the Makassar 1 State Special School. The type of research used is quantitative descriptive. Research data was collected using instruments in the form of questionnaires or questionnaires. The data was analyzed using descriptive and inferential statistics with multiple linear regression formulas in the form of tables, figures, frequencies and narratives processed using SPSS data. Based on the results of the T-test research, the significant variables are attitude, attention, appearance and responsibility. Meanwhile, the F-test shows the value of f-count f-table (172.082 2.35) and a significance level of 0.000 0.05, meaning that there is a simultaneous influence of excellent service on the satisfaction of people with disabilities. The coefficient of determination shows an adjusted R Square value of 0.965, meaning that 95.6% of the satisfaction of people with disabilities can be explained by attitudes, attention, actions, abilities, appearance and responsibility. The remaining 3.5% is explained by other variables that are not in the regression model. This.